PELAKSANAAN UPACARA MAANTA BUBUA DI KANAGARIAN CUPAK KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - Noverina, Delvince; Baidar, Baidar; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2015)
The background of this study is about nowadays the people in Nagari Cupak that involved in cooking the cultural foods only the oldest people above 60 years old, while the people about 40 years old and the teenagers only involved in serving the food. The objectives of this research are to (1) describe the arrangement of the Maanta Bubua ceremony, (2) describe the kind of cultural food of, (3) describe tools that used to bring the cultural food, (4) the meaning of the cultural food. The method used in this study is qualitative method. The arrangement of ceremony in Nagari Cupak has two steps which are preparation before the ceremony and the cultural ceremony of Maanta Bubua. The traditional food and cakes on Maanta Bubua ceremony in Kanagarian Cupak is Nasi, Randang, Apik Ayam, Ayam Goreng, Ikan Goreng, Lemang, Pinyaram, Galamai Kacuik, Nasi Kuning, Kue hias. Special tools that used to bring the cultural food on Maanta Bubua ceremony in Kanagarian Cupak is cambuang, large plate, oval plate, dinner plate, tray or platter. The meaning of cultural food that brought on Maanta Bubua ceremony symbol of hope and desire that you want to accomplish in the future married life.Keyword: Maanta Bubua the procession of ceremony